Deepening the in teraction between industrial and scientiﬁc organisations of the Republic of Belarus in the context of national and global development vectors - Ustinovich, Irina V.; Yakushenko, Ksenia V.; Hrytsevich, Svetlana A. (Journal of the Belarusian State University. Economics, 2024)
The article aims to assume the state of Belarus industrial complex and scientiﬁc organisations and release prospects based on global trends. The research proposes to carry out such an assessment based on the authors’ developed methodology, which includes several mandatory stages: analysis of the current state, identiﬁcation of cooperation areas, assessment of resources and potential, studying legislation and business conditions, assessing opportunities and beneﬁts, strategy development, establishing contacts and communication. The article presents a global overview of the state of industry, identiﬁes global and national development trends, and focuses on the emerging diﬃculties in achieving sustainable growth by industrial enterprises. The foreign experience in the development of enterprises in the context of the formation of industry 4.0 has been studied, and the key drivers that contribute to their sustainable growth, aimed at building adaptive business processes in modern conditions of economic activity, have been identiﬁed. The parameters of the functioning of scientiﬁc and industrial organisations are analysed. The conditions for the transformation of business processes leading to the strengthening of the position of industrial enterprises in the world market are determined, considering such vectors of development as the processes of networking, digitalisation, innovation, and serviceisation, corresponding to the concept of business ecosystems proposed for consideration as strengthening the business potential of enterprises and their further interaction. The applied research methods include a systematic approach and such private methods as synthesis, analysis, modeling, and forecasting.
Keywords: industrial complex; scientiﬁc organisations; trends; state assessment